2008
DOI: 10.3892/or.20.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Human hair follicle and interfollicular keratinocyte reactivity to mouse HPV16-transformed cells: An in vitro study

Abstract: Abstract. The role of stem cells in cancer formation and spreading has been established. As with normal tissue, the cancer stem cells need a special microenvironment to support their growth. This microenvironment may be represented by the tumor stroma. One of the possible ways of tumor stromal formation is the epithelial-mesenchymal transition of tumor epithelium. Following this mechanism, stromal cells must share the basic genetic alterations with the tumor cells. In an attempt to create a system capable of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This observation is corroborated by a practically absent coexpression of keratins with vimentin, a protein that defines the epithelialmesenchymal transition [17,38,39]. The difference between absence of keratin 19 in epidermis positioned over the tumor in BFH in situ and the positive signal from keratinocytes cocultured with fibroblasts prepared from this tumor can be due to differences in the environmental conditions in vitro and in situ, to which fibroblasts from MFH can contribute, similar to fibroblasts from the basal cell carcinoma [16].…”
Section: Discussionmentioning
confidence: 73%
“…This observation is corroborated by a practically absent coexpression of keratins with vimentin, a protein that defines the epithelialmesenchymal transition [17,38,39]. The difference between absence of keratin 19 in epidermis positioned over the tumor in BFH in situ and the positive signal from keratinocytes cocultured with fibroblasts prepared from this tumor can be due to differences in the environmental conditions in vitro and in situ, to which fibroblasts from MFH can contribute, similar to fibroblasts from the basal cell carcinoma [16].…”
Section: Discussionmentioning
confidence: 73%
“…However, other cell types, including the hypothetical source in cancer cells per se after epithelial-mesenchymal transition, cannot be fully excluded as the source cells [14,15,16], assuming CAF derived from the cancer cells would carry the same genetic alterations or HPV-16 oncogenes. In vitro experiments demonstrated that lung epithelial cells transfected with HPV-16 genes E6 and E7 acquired the mesenchymal phenotype and exhibited remarkable biological effects on co-cultured keratinocytes that are phenotypically similar to cancer cells [17]. However, other experiments demonstrated that origination of CAF from cancer cells is not too probable [14].…”
Section: Tumour As a Complex Ecosystem Supporting Function Of The mentioning
confidence: 99%
“…Moreover, HPV16 transformed lung epithelial cells are oncogenic and they acquire typical fibroblastic phenotype. When cocultured with normal human keratinocytes, normal keratinocytes acquire features very similar to cancerous cells [ 85 ]. On the other hand, human cancer cells grafted to nu/nu mice form tumors with stroma containing exclusively fibroblasts of the mouse origin, as was demonstrated by use of human-specific anti-vimentin antibodies [ 86 ].…”
Section: Cafs As the Master Cell Type In Tumor Stromamentioning
confidence: 99%